Both the Complexity of Tight Junctions and Endothelial Transcytosis Are Increased During BBB Postnatal Development in Rats - Li, Wei; Zou, Jinlong; Shang, Junkui; Gao, Chenhao; Sun, Ruihua; Liu, Ruijie; Cao, Huixia; Wang, Yanliang; Zhang, Jiewen (Frontiers in Neuroscience, 2022)
The blood-brain barrier (BBB) comprises a single layer of endothelial cells and maintains a safe and homeostatic environment for proper neuronal function and synaptic transmission. BBB is not a discrete physical barrier, but a complex, dynamic, and adaptable interface. BBB continues to mature under the influence of the neural environment within a short period of time after birth. However, the basic mechanism of BBB formation and maintenance remains a mystery. Early studies have identified two structural characteristics of microvascular endothelium: special tight junctions (TJs) and a very low transcellular vesicle transport rate. Previous studies believed that BBB damage was mainly due to the destruction of tight junctions, and the role of vesicle transcytosis was neglected, so there was a lack of research on its impact on blood-brain barrier. It is urgent to get a better clarification of the unique structural and functional characteristics of the BBB endothelium to explain the role of BBB injury in neurological diseases. RNA sequencing was used to study the molecular characterization of cerebral cortex vascular endothelium by isolating them from neonatal, adolescent and adult rats. For investigation the maintenance mechanism of the BBB, we focused on the cellular and molecular regulation of barrier formation and the two characteristics of microvascular endothelial cells. Interestingly, we found that during the development of the blood-brain barrier, although the tight junctions gradually mature, endothelial cell transcytosis is gradually enhanced, resulting in an increase in the permeability of the blood-brain barrier. This study suggested that under physiological conditions, low vesicle transport is playing an important role in maintaining the integrity of the blood-brain barrier. This study not only summarized the unique characteristics of microvascular endothelial cells, but also illustrated a clarified mechanism of the development and maintenance of BBB which can provide new therapeutic opportunities for central nervous system drug delivery. Raw data of RNA sequencing were deposited in NCBI Sequence Read Archive database (PRJNA790676).